Does topic choice affect high-stakes L2 writing scores? - Amengual-Pizarro, Marian (Complutense Journal of English Studies, 2023)
This study sets out to investigate the potential effects of topic choice on test-takers’ L2 writing scores in a high-stakes context. Data were collected from a total of 150 essays that were assessed by three qualified raters who participated as judges in the administration of the high-stakes English Test (ET), included in the Spanish University Admission Examination (SUAE), in July 2020. Although test-takers showed a clear preference for one writing topic choice over the other, results did not reveal statistically significant differences between the average scores awarded to both essay options. Therefore, the data clearly indicate that topic choice does not affect L2 writing quality. Findings also show that choice of topic had little impact on test-takers’ overall performance on the ET. Additionally, no differences in choice patterns were either observed across test-takers’ proficiency levels, which suggests that topic choice may be closely related to test-takers’ characteristics (motivation, interest, relevance, etc.) rather than to the writing prompt itself. Lastly, the data show potential interactions between raters’ characteristics and essay topics which may affect final writing scores.